PREFERENSI MASYARAKAT TERHADAP PEMANFAATAN HUTAN DI DESA LABUAN KUNGGUMA KECAMATAN LABUAN KABUPATEN DONGGALA - Sugara, Bayu; Malik, Adam; Massiri, Sudirman Dg.; Anwar, Anwar (Universitas Tadulako, 2020)
Forests and surrounding communities are two components of the ecosystem that must be prioritized for attention in an effort to ensure sustainable management of forest resources. Sustainable forest resources are expected to provide life insurance for the surrounding community. The life of the village community around the forest cannot seek from the existence of the forest where they depend for their livelihood, the forest is a source of fulfillment of their daily needs and a source of family income. The purpose of this study aims to see people's preferences for forest use in Labuan Kungguma Village, Labuan District, Donggala Regency. This research was conducted for two months, from October to December 2016. The research location was located in Labuan Kungguma Village, Labuan District, Donggala Regency. The research method used a survey method, which describes quantitatively the tendency of preferences for the use of forest resources from a community population in Labuan Kungguma Village, Labuan District, Donggala Regency. The types and sources used are primary data and secondary data. The number of respondents who will be interviewed in this study in 30 households, using the assessment method. Respondents were selected using simple random sampling method. The results of the research in Labuan Kungguma Village, Labuan District, Donggala Regency, show that the highest preference for forest use for the community in Labuan Kungguma Village is the use of production forests as a source of land for gardening, processing wood pads, and rattan collectors.Keywords: Preference, Forest Utilization, Local Communities, Production Forest